2021
DOI: 10.1007/s12351-021-00658-x
|View full text |Cite
|
Sign up to set email alerts
|

On the predictive power of CAPE or Shiller’s PE ratio: the case of the Greek stock market

Abstract: This paper examines the capability of the Cyclically Adjusted Price to Earnings (CAPE) or Shiller's P/E ratio, along with other relative valuation ratios such as the P/E and the P/BV, to predict future returns of the FTSE/ASE Large Cap Index, starting from the development of the index (1997) to December 2018. We have herein used several regression models in order to examine the relationship between the above ratios and the future returns of 1, 3, 5 and 10 years. We show that, while P/E and P/BV ratios are not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…, 2018). The knowledge about the target firm's future performance can be taken into consideration by investors in their attempt to determine the intrinsic value of each security in order to identify investment opportunities (Kenourgios et al. , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2018). The knowledge about the target firm's future performance can be taken into consideration by investors in their attempt to determine the intrinsic value of each security in order to identify investment opportunities (Kenourgios et al. , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Past research discussed the effect of earnings management on the future earnings and stock market performance, either using accrual-based methods (Rangan, 1998;Teoh et al, 1998;DuCharme et al, 2004;Lim et al, 2008) or real-activities manipulations (Graham et al, 2005;Cohen et al, 2008;Gunny, 2010;Kothari et al, 2016;Jiang et al, 2018). The knowledge about the target firm's future performance can be taken into consideration by investors in their attempt to determine the intrinsic value of each security in order to identify investment opportunities (Kenourgios et al, 2021). Louis (2004) verified the negative impact of accruals earnings management on the acquirer's underperformance, while Farooqi et al (2017) EMJB 18,4 confirmed that real earnings management reversals are negatively related to acquiring firm's performance.…”
Section: Effect Of Corruption In Target Firmsmentioning
confidence: 99%
“…They found that the sales-to-price metric and their composite model improved their prediction of 10-year stock returns in the S&P500 and resulted in a correlation between out-of-sample forecasts and actual returns of 0.87 and significantly reduced the standard deviation of the forecast error. Kenourgios, Papathanasiou, & Bampili (2021) published a study on the predictive ability of the CAPE ratio in the Greek stock market, using both five and ten years of trailing real earnings for the Athens Stock Exchange Large Cap Index. The authors found that the CAPE ratio appeared to be the best predictor of stock market returns only for long-term returns, and its ability to predict returns diminished as the return's horizon shortened.…”
Section: Cape Valuation Abilitymentioning
confidence: 99%
“…This analysis was conducted by establishing the Pearson's coefficient for these variables and the results thereof, tabled for discussion in the form of a heatmap again. Several other authors use correlations to test the relationships between similar variables, including Kenourgios et al (2021), Jivraj & Shiller (2017) and Algaba & Boudt (2017).…”
Section:  Consumer Price Inflation Index (Cpi)mentioning
confidence: 99%
See 1 more Smart Citation